PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA DENGAN SELF-EFFICACY SEBAGAI VARIABEL MEDIASI PADA SISWA SMKN 1 SURABAYA - Suci Ainun Ni'mah; Novi Marlena (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
This study aims to analyze the effect of entrepreneurship education on entrepreneurial interest, with self-efficacy as a mediating variable, among students at SMKN 1 Surabaya. The background of the study is based on the high unemployment rate among Vocational High School (SMK) graduates, indicating that graduates are not fully prepared to face the world of work or create jobs independently. This study used a quantitative approach with an explanatory research design. The sample consisted of 206 students selected using a simple random sampling technique. Data were collected through a questionnaire using a five-point Likert scale and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results showed that entrepreneurship education had a positive and significant effect on self-efficacy and entrepreneurial interest. Furthermore, self-efficacy also significantly influenced entrepreneurial interest and was proven to mediate the effect of entrepreneurship education on entrepreneurial interest. These findings confirm that the success of entrepreneurship education depends not only on cognitive aspects and skills but also significantly on students' psychological aspects, particularly self-efficacy. The implications of this study demonstrate the importance of strengthening experiential learning to increase students' confidence in entrepreneurship. Keywords: Interest in Entrepreneurship; Entrepreneurship Education; Self-Efficacy